2.5k views
15 votes
Help? I tried the first two, can't get them. I don't know how I got the third.

Help? I tried the first two, can't get them. I don't know how I got the third.-example-1

2 Answers

4 votes

Answer:

Explanation:


x(6x+14)-8(6x+14)\\6x^2+14x-48x-112\\

Rest, you have to substitute the value. Such as A= -112

User Richs
by
4.5k points
10 votes

Answer:

See below

Explanation:

(6x+14)(x-8) = Expand

6x^2 - 48x + 14x - 112 =

6x^2 - 34x-112 A = 6 B = -34

User Zooglash
by
5.0k points